Recent Advances in the Electrochemical Functionalization of Isocyanides. Issue 1 (20th September 2022) - Gu, Qingyun; Cheng, Zhenfeng; Qiu, Xiaodong; Zeng, Xiaobao
Abstract: Isocyanides are well‐known as efficient CO surrogates and C1 synthons in modern organic synthesis. Although tremendous efforts have been devoted to fully exploiting the reactivity of isocyanides, these transformations are primarily limited by their utilization of stoichiometric toxic chemical oxidants. With the recent resurgence of organic electrochemistry, which has considerably laid dormant over the past several decades, electrolysis has been identified as a green and powerful tool to enrich structural diversity by solely utilizing electric current as clean and inherently safe redox equivalents of stoichiometric chemical oxidants. In this regard, the unique reactivity of isocyanides has been studied in numerous electrochemical transformations. This review comprehensively highlights the most relevant progress in electrochemical strategies towards the functionalization of isocyanides up until June of 2022, with a focus on reaction outcomes and mechanisms. Abstract : The chameleonic reactivity of isocyanides in numerous electrochemical transformations has been reviewed herein according to the general reaction modes of isocyanides. Each section will include a critical discussion of the previous studies, along with elucidation of mechanistic insights.